High‐pressure behavior and P‐induced phase transition of CaB3O4(OH)3·H2O (colemanite). Issue 5 (23rd February 2017) - Lotti, Paolo; Gatta, Giacomo Diego; Comboni, Davide; Guastella, Giorgio; Merlini, Marco; Guastoni, Alessandro; Liermann, Hanns‐Peter
Abstract: Colemanite (ideally CaB3 O4 (OH)3 ·H2 O, space group P 21 / a, unit‐cell parameters: a ~ 8.74, b ~ 11.26, c ~ 6.10 Å, β ~ 110.1°) is one of the principal mineralogical components of borate deposits and the most important mineral commodity of boron. Its high‐pressure behavior is here described, for the first time, by means of in situ single‐crystal synchrotron X‐ray diffraction with a diamond anvil cell up to 24 GPa (and 293 K). Colemanite is stable, in its ambient‐conditions polymorph, up to 13.95 GPa. Between 13.95 and 14.91 GPa, an iso‐symmetric first‐order single‐crystal to single‐crystal phase transition (reconstructive in character) toward a denser polymorph (colemanite‐II) occurs, with: a COL‐II =3· a COL, b COL‐II = b COL, and c COL‐II =2· c COL . Up to 13.95 GPa, the bulk compression of colemanite is accommodated by the Ca‐polyhedron compression and the tilting of the rigid three‐membered rings of boron polyhedra. The phase transition leads to an increase in the average coordination number of both the B and Ca sites. A detailed description of the crystal structure of the high‐ P polymorph, compared to the ambient‐conditions colemanite, is given. The elastic behaviors of colemanite and of its high‐ P polymorph are described by means of III‐ and II‐order Birch‐Murnaghan equations of state, respectively, yielding the following refined parameters: K V 0 =67(4) GPa and K V ′=5.5(7) [β V 0 =0.0149(9) GPa −1 ] for colemanite; K V 0 =50(8) GPa [β V 0 =0.020(3) GPa −1 ] for its high‐ P polymorph.